Legal Protection Against Consumers Who Do E-Commerce Buying and Selling Transactions Through the WeChat Platform - Radea Respati Paramudhita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Along with development digital technology, WeChat does not onlyfunctioning as application communication, but also as an e-commerceplatform used For transact online. This is present various challenges,including risk for consumer like fraud, personal data breaches, and lackof clarity about rights and obligations of the parties. Research Thisaiming for analyze protection law to consumer in transaction sell buythrough the WeChat platform. Research This use approach lawempirical that is a method procedures used For solve problem withresearching secondary data formerly Then to be continued with usestudy on primary data. Research carried out in the city of Bandung withgive questionnaire to respondents who have using the WeChat platformin transaction sell buy. Research results show transaction sell buythrough the WeChat platform basically similar with sell buyconventional, only done in a way electronics and have runway valid lawbased on the Civil Code and the ITE Law, with condition fulfillmentagreement free, the ability of the parties, the object certain, and lawfulpurposes. Information electronics produced acknowledged as tool prooflaw, giving certainty law for consumers and actors business . Protectionconsumer set up through the UUPK, ITE Law, and PP Number 71 of2019, which guarantees right consumer For get information transparentas well as compensation If happen loss consequence default, withsanctions firm for perpetrator business that violates the contract.electronics must also be fulfil standard law, including use Indonesianlanguage and clear provisions. Regulation This expected createecosystem safe, fair and trusted digital trading , with provide a sense ofsecurity for consumer as well as push not quite enough answerperpetrator business